Penerapan Model Pembelajaran Teams Games Tournament (TGT) untuk Meningkatkan Minat Belajar Peserta Didik Kelas V SDN Landah - Pransisca , Made Ayu; Pahru , Syaipul (Lembaga Bale Literasi, 2024)
This research aims to determine whether or not there is an increase in learning interest in class V students when using the themed games tournament (TGT) learning model. The type of research used in this research is classroom action research (PTK) with class V research subjects consisting of 30 students at SDN Landah. Meanwhile, the object of this research is students' interest in learning after implementing the Teams Games Tournament (TGT) learning mode. Based on the research results, it was found that during the pre-cycle implementation, the percentage of students who had a high interest in learning was 32% of the total number of students. After implementing the learning model in cycle 1 there was an increase of 16.67% so that the percentage of student interest rose to 50%. From cycle 1 to cycle 2 there was another increase of 33.33% so that the final percentage of interest in learning from all students was 83.33%. Basedon the results of these data, it can be concluded that the application of the teams games tournament (TGT) learning model can increase the learning interest of class V students at SDN Landah.